Numerical investigation of flow field around T-shaped spur dyke in a reverse-meandering channel - Tripathi, Ravi Prakash; Pandey K.K. (IWA Publishing, 2022)
n this paper, the flow characteristics around T-shape spur dyke situated in the reverse meandering channel with a rigid bed is simulated using renormalization group (RNG) k -ϵ turbulence model with ANSYS 2018 Fluent software. To solve the model in 3D ways we used Navier-Stroke's equation based on the principle of conservation of mass and momentum within a moving fluid. For studying the flow characteristics, computational fluid dynamics were applied with all geometric parameters and the turbulence was simulated using (RNG) k -ϵ equations of model. In this simulation, the structured meshes were used with different diameters and diameters of meshes are high at the exit channel for obtaining accuracy in the result. In this study, we mainly focus on the effect of Froude number on flow pattern and several other characteristics like velocity distribution, flow separation, bed-shear-stress distribution. The final result of this research work is compared with the condition when no structure is present in the channel.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Channel bend; Flow field; Meandering channel; Scour; Spur dyke; Turbulence model; Computational fluid dynamics; Flow patterns; Flow separation; Shear flow; Shear stress; Statistical mechanics; Turbulent flow; surface water; Equation based; Flow characteristic; FLUENT software; Meandering channel; Navier-strokes equations; Numerical investigations; Renormalization group; Spur dyke; T shapes; Froude number; Navier-Stokes equations; software; turbulence